The government spending on education and health, and its impact on sustainable development in Sudan between (1995 - 2015) - Zeinelabdin, Elham Ahmed Ibrahim; Haj Alhade, Muslema Murtada Yousef; Alkhabir, Minas Abdelrahman Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
The study dealt with government spending on education and health and its impact on sustainable development, and limits of the study were Sudan between 1995 and 2015 sustainable. The study aims to know the effect of education and health in supporting sustainable development in Sudan. The study followed the descriptive analytical approach in terms of information collection, presentation of relevant data, and the views standard economy The most important findings of the study were the lack of government spending on education and health through the weakness of the selection factor in the two equations which led to the failure of education to harmonize the demands of the labor market and the lower expectation of age rates, the higher the government expenditure on education and health, the higher the rate of economic and social growth with a healthy environment and reduced illiteracy, leading to increased rates of sustainable government. The study made several recommendations, the most important of which were the need to increase government spending on education and health to achieve sustainable government in Sudan.